The Relevance of Al-Syahrastani's Al-Milal wa Al-Nihal Methodology to Contemporary Islamic Historiography - Haif, Abu; Ansar, Andi Lifiani; Ibrahim, Islahuddin; Sibghatullah, Abdurrahman; Kaharu, Ninin Rizka Syahfitri; Darmawan, Darmawan (JUSPI (Jurnal Sejarah Peradaban Islam), 2025)
The purpose of this study is to analyse the methodology and contributions of Al-Syahrastani's book Al-Milal wa Al-Nihal in Islamic historiography. This study is a literature review or bibliographic study using a descriptive qualitative approach and research on scientific articles and books relevant to this study. Al-Milal wa Al-Nihal by Al-Syahrastani was studied to explore its methodology's relevance and contribution to Islamic historiography. The results of the study indicate that by using a comprehensive descriptive analysis methodology and in-depth comparisons, there are no biased research results, which ultimately led to the book Al-Milal wa al-Nihal as the first work that objectively and systematically organises and presents the history of various religious sects and philosophical schools of thought. The conclusion of this study states that Al-Milal wa Al-Nihal by Al-Syahrastani is a highly significant contribution in maintaining the objectivity of historical writing and can be used as a reference in the study of Islamic historiography.